Short-term effects of various ozone metrics on cardiopulmonary function in chronic obstructive pulmonary disease patients: Results from a panel study in Beijing, China. (January 2018) - Li, Hongyu; Wu, Shaowei; Pan, Lu; Xu, Junhui; Shan, Jiao; Yang, Xuan; Dong, Wei; Deng, Furong; Chen, Yahong; Shima, Masayuki; Guo, Xinbiao
Abstract: Background: Short-term exposure to ambient air pollution has been associated with lower pulmonary function and higher blood pressure (BP). However, controversy remains regarding the relationship between ambient multiple daily ozone (O3 ) metrics and cardiopulmonary health outcomes, especially in the developing countries. Objectives: To investigate and compare the short-term effects of various O3 metrics on pulmonary function, fractional exhaled nitric oxide (FeNO) and BP in a panel study of COPD patients. Methods: We measured pulmonary function, FeNO and BP repeatedly in a total of 43 patients with COPD for 215 home visits. Daily hourly ambient O3 concentrations were obtained from central-monitoring stations close to subject residences. We calculated various O3 metrics [daily 1-h maximum (O3 -1 h max), maximum 8-h average (O3 -8 h max) and 24-h average (O3 -24 h avg)] based on the hourly data. Daily indoor O3 concentrations were estimated based on estimated indoor/outdoor O3 ratios. Linear mixed-effects models were used to estimate associations of various O3 metrics with cardiopulmonary function variables. Results: An interquartile range (IQR) increase in ambient O3 -8 h max (80.5 μg/m 3, 5-d) was associated with a 5.9% (95%CI: −11.0%,  −0.7%) reduction in forced expiratory volume in 1 s (FEV1 ) and a 6.2% (95%CI: −10.9%,  −1.5%) reduction in peak expiratory flow (PEF). However, there were no significant negative associations between ambient O3 -1 h max, O3 -24 h avg and FEV1, PEF. An IQR increase in ambient O3 -1 h max (85.3 μg/m 3, 6-d) was associated with a 6.7 mmHg (95%CI: 0.7, 12.7) increase in systolic BP. The estimated indoor O3 were still significantly associated with reduction of FEV1 and PEF. No significant associations were found between various O3 metrics and FeNO. Conclusions: Our results provide clues for the adverse cardiopulmonary effects associated with various O3 metrics in COPD patients and highlight that O3 -8 h max was more closely associated with respiratory health variables. Graphical abstract: Highlights: O3 pollution level is increasing in Beijing China. Associations between various O3 exposure metrics and cardiopulmonary function in COPD patients were evaluated. O3 daily maximum 8-h average was associated with decreased FEV1 and PEF. O3 exposure can pose threat to respiratory health with pollution level lower than the national O3 standard. Abstract : O3 exposure can pose threat to respiratory health with pollution level lower than the national O3 standard in Beijing, China.